MICROZONASI GEMPA WILAYAH PALEMBANG TERHADAP STRUKTUR RANGKA MOMEN BETON BERTULANG - Yunus, Ishak; Firdaus, Firdaus; Rosyad, Farlin; Kasmuri, Mudiono; Mangalik, Yefta Peter (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2016)
One of the main problem building civil engineering standing on a land is an the size of the could not estimated by definite and time that cannot be predicted properly.That is why planning structure earthquake resistant the further development of the until now.3 (three) parameter important in earthquake sni 03-1726-2012 namely the ss, an undergraduate degree, and klafikasi land.Zone earthquake in the city of palembang having 2 (two) klafikasi land the land moderate and the soft land, where parameter the acceleration of the bedrock maximum to soil and he the ss = 0.259 and an undergraduate degree = 0.163), and the soft land of (the ss = 0.282 and an undergraduate degree = 0.173).On the ground and the acceleration of the bedrock maximum in kecamatan ilir east ii (the ss = 0.259 and an undergraduate degree = 0.163) and acceleration the bedrock minimum in kecamatan sako (the ss = 0.251 and an undergraduate degree = 0.160).On soft ground the acceleration of the bedrock maximum in kecamatan kertapati (the ss = 0.288 and an undergraduate degree = 0.164) and acceleration the bedrock (the ss and an undergraduate degree) minimum in kecamatan ilir east ii (the ss = 0.262 and an undergraduate degree = 0.164).